Tracking Children's Print-Processing Skill Across Grades 1–3: Implications for Reading Assessment and Instruction. Issue 8 (17th November 2018) - Morris, Darrell; Trathen, Woodrow; Perney, Jan; Gill, Tom; Schlagal, Robert; Ward, Devery; Frye, Elizabeth
Abstract : Grounded in the simple view of reading, this study tracked the development of print-processing skill in high-, average-, and low-achieving readers at six time points across grades 1–3. Results showed large between-group differences in sight vocabulary, oral reading accuracy, and oral reading rate that remained stable from beginning of first grade to end of third grade. While the average group consistently met pre-set instructional-level criteria for oral reading accuracy and rate, the low group did not. Implications for assessment and instruction are provided.